Procedural rigidity vs. bureaucratic adaptability: A comparative analysis of formalization in new regions and parent regions - Zarni Adia Purna (Department of Government Science, 2025)
The wave of regional expansion in Indonesia has created new dynamics in the evolution of local government bureaucracy, especially in the balance between procedural formalization and organizational adaptability. This study analyzes the comparison of procedural rigidity versus bureaucratic adaptability between new autonomous regions (DOB) and parent regions in the context of the expansion of Buton Regency. Using a mixed methods design with a comparative case study approach, involving 270 respondents from Buton, South Buton, and Central Buton Regencies. Data were collected through structured surveys, in-depth interviews, participant observation, and document analysis. The results showed that the Buton Regency showed the highest formalization (4.12) but the lowest adaptability (3.52), while both DOBs showed superior adaptability (3.94 and 3.87) with more moderate formalization. The parent region experienced a strong negative trade-off (r=-0.48) between formalization and adaptability, while DOB showed a more complex and less linear relationship. As a result, DOB managed to achieve a more optimal balance through fresh start advantage, while the parent region experienced institutional lock-in that hampered adaptability. This finding challenges the assumption that institutional maturity always contributes positively to organizational effectiveness.